ANALISIS KESADARAN MATEMATIS SISWA DALAM PEMBELAJARAN SNOW CUBE THROWING BERBASIS EKSPLORASI - Nenden Mutiara Sari (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2021)
The snow cube throwing learning model was developed with the aim of making students appreciate the usefulness of mathematics in everyday life. In accordance with the characteristics of this learning model, students are given various types of contextual teaching materials that aim to make students have good mathematical awareness. This study aims to analyze the mathematical awareness of students who receive snow cube throwing (SCTBE) learning based on exploration in terms of school categories. This study is a mix-method study with an explanatory sequential design. The research subjects were students of class VIII from three schools in Cimahi City. The results showed that: (1) SCTBE learning had the same impact on students' mathematical awareness in each school category. In other words, all students who receive SCTBE learning have the same awareness of the usefulness of mathematics in daily life, future studies and careers; and (2) The results of the analysis on each indicator show that the students' mathematical awareness in each school category is classified as good.